HADIS DAN PERUBAHAN SOSIAL - Muttaqin, Zainal (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2020)
Legal changes that exist in a society always have two functions, namely the law that functions as social engineering and the law that functions as social control. In its function as social engineering, law plays a role in creating changes in social structures and spurring people to be willing and able to move. Whereas in its function as social control, the law plays the opposite role, namely maintaining social stability, controlling the direction and controlling the pace of change in society so as not to get out of the provisions of the applicable provisions. It is in this last function that the law is always considered to be lagging behind the change itself. On the one hand, the law is considered to curb various activities in society, on the other hand, the dynamics of society always demand that the law adapts to the needs of the times. In the Indonesian context, disputes over the use of hadith have also become problems that are not limited to theological issues, but have widened to become social issues. This is almost the case in all areas of Islamic law which are commonly known as khilafiyah problems, among others, such as the provisions on whether or not to perform qunut in the Fajr prayer, tarawih and witr prayers eleven or twenty-three cycles, determining the start of Ramadan and beginning of Shawwal. The problem started, among other things, from the existence of contradictory hadiths and the existence of different interpretations of each hadith. This is where the need to return to the ijtihad movement in the field of hadith in an effort to reform Islamic law.Keywords: hadith, changes of laws